THE MARKETING MIX STRATEGY ANALYSIS TO ATTRACT PROSPECTIVE STUDENTS IN SELECTING PROGRAMS IN ISLAMIC INSTITUTE OF SULTAN MUHAMMAD SYAFIUDDIN – SAMBAS - Budi Iswanto (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
The service marketing mix strategy is important to improve the Islamic high school. The integrated service marketing strategies from higher education institutions is a major factor in attracting prospective students which requires the Islamic Institute of Sultan Muhammad (IAIS) - Sambas to act professionally in every academic activity. The problem of this research was to analyze the effect of integrated marketing approach program consisting of; study programs, tuition fees, location, promotions, employees, physical facilities, accreditation status, reputation, alumni, leadership, students, research and publications, and other tridarma activities on decisions and attractiveness of prospective students to choose IAIS Sambas. This study aimed to determine the effect of a service program marketing integrated strategy on the attractiveness of students choosing IAIS Sambas as their college campus candidate. To find out how the service program's mixed strategy was affected, a series of structured interviews were conducted with 205 prospective students with a sample - Proportionate Stratified Random Sampling to Islamic Religious Education students (Independent Class and Transfer Class students). In addition to interviews, data collection was also carried out through questionnaires with Liker scale measurement units under the case study approach. After the data was collected, quantitative descriptive analysis was carried out; coding, revision, evaluation, in-depth interpretation and drawing conclusions to prove the findings of this study in accordance with the formulation of the research question as to get the validity and reliability of these findings. Finally, we can conclude that joint or integrated marketing strategy of study programs, tuition fees, location, promotion, staffing, learning facilities, alumni, accreditation, teaching staff and academic community activities, which together have a significant influence on decisions and the attractiveness of prospective students in choosing courses at IAIS Sambas.